Tunable synthesis of self-assembled cyclic peptide nanotubes and nanoparticles1. Issue 19 (21st May 2015) - Sun, Leming; Fan, Zhen; Wang, Yongzhong; Huang, Yujian; Schmidt, Michael; Zhang, Mingjun
<x xml:space="preserve">Abstract</x> Different sizes and morphologies of cyclic peptide self-assembled nanostructures were obtained through phase equilibrium, pH-driven, and pH-sensitive methods.